Cattle serologically positive for Brucella abortus have antibodies to B. abortus Cu-Zn superoxide dismutase. - Tabatabai, L B (1994)
In this study, we demonstrated by a Cu-Zn superoxide dismutase-specific enzyme-linked immunoassay that cattle that are serologically positive for Brucella abortus have serum immunoglobulin G antibodies to B. abortus Cu-Zn superoxide dismutase. The specificity of the antibody reactivity was confirmed by Western blot (immunoblot) analysis with B. abortus salt-extractable proteins containing native Cu-Zn superoxide dismutase and with recombinant B. abortus Cu-Zn superoxide dismutase. The results represent a first step in the direction of the development of a multiprotein diagnostic reagent for bovine brucellosis.